2001
DOI: 10.1046/j.1528-1157.2001.28700.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Oromotor Deficits in Children with Benign Childhood Epilepsy with Central Temporal Spikes

Abstract: Summary:Purpose: To describe transient oromotor deficits in benign childhood epilepsy with centrotemporal spikes (BCECTS), an idiopathic age-specific epileptic syndrome with a benign course.Methods: Five children with BCECTS and intermittent dysarthria and drooling not in the context of typical clinical seizures are presented.Results: The periods of oromotor deficits correlated with increased seizure frequency in all children. Concomitant EEGs that were recorded during periods of dysarthria in four of the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
12
1
1
Order By: Relevance
“…Conversely, other studies have shown language dysfunction in children with RE (Deonna et al 1993(Deonna et al , 2000Staden et al 1998). Difficulties in word-retrieval have been reported , Kramer et al 2001 which contradicts the present study in which the Rapid Confrontation Naming test was used. Staden and colleagues (1998) included a dyspraxia screening and this revealed abnormality in nine of 20 children, most frequently concerning lip and tongue movements and difficulties in articulating a sequence of syllables.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, other studies have shown language dysfunction in children with RE (Deonna et al 1993(Deonna et al , 2000Staden et al 1998). Difficulties in word-retrieval have been reported , Kramer et al 2001 which contradicts the present study in which the Rapid Confrontation Naming test was used. Staden and colleagues (1998) included a dyspraxia screening and this revealed abnormality in nine of 20 children, most frequently concerning lip and tongue movements and difficulties in articulating a sequence of syllables.…”
Section: Discussioncontrasting
confidence: 99%
“…The optimal function of the auditory Oromotor Performance in Rolandic Epilepsy Staffan Lundberg et al 607 perception may be disturbed if there is a maturational dependent dysfunction of essential pathways, including EEG activity. The oromotor dysfunction reported in studies of intense or 'acute' RE (Roulet et al 1989, Boulloche et al 1990, Deonna et al 1993, Kramer et al 2001) was positively correlated with increased bilateral synchronous or asynchronous rolandic discharges. In the present study, bilateral rolandic discharges did not occur synchronously.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These three patients resemble those in other sporadic reports of transient neurologic dysfunction of epileptic origin in children with typical BCECTS (1–5,8–11). The clinical presentation was variable and involved a combination of slurred speech, continuous drooling, oromotor dyspraxia, atonic head nods, or facial myoclonia.…”
Section: Discussionsupporting
confidence: 81%
“…Other atypical forms of BCECTS include benign childhood epilepsy with centrotemporal spikes with frequent refractory seizures (Lerman & Kivity, 1975; Loiseau et al., 1988; Kramer et al., 2002), the “classic” atypical variant of BCECTS (Aicardi & Chevrie, 1982; Fejerman et al., 2000), status epilepticus of BCECTS (Fejerman & Di Blasi, 1987), BCECTS with transient oromotor dysfunction (Roulet et al., 1989; Deonna et al., 1993; Kramer et al., 2001; Dubois et al., 2003), and BCECTS presenting as falls (Watemberg et al., 2009). The “classic” atypical form usually presents as severe aggravation, but in contrast to ESES and LKS, the cognitive outcome is always favorable (Fejerman et al., 2007).…”
Section: Atypical Formsmentioning
confidence: 99%